MitraClip for High-Risk Patients with Significant Mitral Insufficiency: Shall We Unreservedly Recommend It? - Ostovar, Roya; Claus, Thomas; Hartrumpf, Martin; Kuehnel, Ralf Uwe; Braun, Christian; Butter, Christian; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2018)
Background MitraClip (Abbott Inc.) is propagated as a palliative option for high-risk patients with mitral insufficiency considered not qualifying for surgical repair. A proportion of patients requires consecutive surgery because of technical failure or inappropriate clinical improvement. Furthermore, surgical reconstruction is impossible in almost all patients after MitraClip implantation. Consequently, these patients receive replacement although primary repair may have been possible. The outcome of those patients compared with patients receiving primary mitral valve replacement (MVR) or mitral valve repair (MVP) was analyzed.Methods A total of 23 patients were retrospectively analyzed after MVR following MitraClip. Overall, 46 patients with corresponding demographic data and risk profile receiving primary MVR (23 patients) or MVP (23 patients) were retrieved for matched pair analysis.Results Mean age was 70 years in all groups, log European system for cardiac operative risk evaluation (EuroSCORE) was 22.47% ± 16.30 in MVR after MitraClip (MC), 22.34% ± 16.23 in MVP, and 22.33% ± 16.14 in MVR group. Preoperative left ventricular ejection fraction (LVEF) was 44%, and postoperative LVEF was 48% in all groups. The 30-day mortality was 21.7% in the MitraClip group whereas it was 4.3% in the MVR and 13.0% in the MVP group. The 1-year survival was 56.5% in the MitraClip group while it was 95.6% in the MVR group and 82.6% in the MVP group (Wilcoxon test: p = 0.007; chi-square test: p = 0.001 MitraClip vs. MVR; p = 0.054 MitraClip vs. MVP).Conclusions Patients requiring surgical MVR after the previous MitraClip fared worse than matched cohorts receiving primary MVR or MVP. Indication for MitraClip should, therefore, be made very cautiously given the excellent results gained with primary surgery.
Keywords: mitral valve surgery; heart valve surgery; outcomes